The REVIEW OF ARTIFICIAL INTELLIGENCE AND HUMAN THINKING - Rachna Rajput , Chamkour Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Many fields, including formal logic, probability theory, decision theory, management science, linguistics, and philosophy, have contributed to the development of tools and approaches of AI research. The implementation of these disciplines in AI, on the other hand, has marked the beginning of several innovations and extensions. Computational logic approaches are among the most powerful of these. Computational logic integrated in an agent cycle, according to the study, incorporates and enhances both conventional logic and classical decision theory. Many of these approaches in the study may be applied not just in AI, but also in everyday life to help individuals improve their own intelligence without the help of computers, according to the authors.